Crystal structure of morimotoite from Ice River, Canada. Issue 4 (30th April 2014) - Antao, Sytle M.
<x content-type="archive" xml:space="preserve">Abstract</x> The crystal structure of a morimotoite garnet, ideally Ca3(Ti4+Fe2+)Si3O12, from the Ice River alkaline complex, British Columbia, Canada was refined by the Rietveld method, space group <alternatives><inline-graphic xlink:href="ark:/27927/pgj46r65qb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[Ia3 d]]> </alternatives>, and monochromatic synchrotron high-resolution powder X-ray diffraction (HRPXRD) data. Electron-microprobe analysis indicates a homogeneous sample with a formula Ca2.91Mg0.05Mn2+0.03Σ3[Ti1.09Fe3+0.46Fe2+0.37Mg0.08]Σ2(Si2.36Fe3+0.51Al0.14)Σ3O12. The HRPXRD data show a two-phase intergrowth. The reduced χ2 and overall R(F2) Rietveld refinement values are 1.572 and 0.0544, respectively. The weight percentage, unit-cell parameter (Å), distances (Å), and site occupancy factors (sofs) for phase-1 are as follows: 76.5(1)%, a = 12.156 98(1) Å, average <Ca–O> = 2.4383, Ti–O = 2.011(1), Si–O = 1.693(1) Å, Ca(sof) = 0.943(2), Ti(sof) = 0.966(2), and Si(sof) = 1.095(3). The corresponding values for phase-2 are 23.5(1)%, a = 12.160 67(2) Å, average <Ca–O> = 2.452, Ti–O = 1.988(3), Si–O = 1.704(3) Å, Ca(sof) = 1.063(7), Ti(sof) = 1.187(7), and Si(sof) = 1.220(8). The two phases cause strain that arises from structural mismatch and gives rise to low optical anisotropy. Because the two phases are structurally quite similar, a refinement using a single-phase model with anisotropic displacement parameters shows no unusual displacement ellipsoid for the O atom that requires a "split O-atom position", as was done in previous studies.